Investigation of soil compaction on yield and agronomic traits of wheat under saline and non-saline soils. Issue 10 (24th August 2018) - Shahrayini, Elham; Fallah, Mahboobeh; Shabanpour, Mahmoud; Ebrahimi, Eisa; Saadat, Saeid
ABSTRACT: Inappropriate crop management and long-term use of heavy agricultural equipment can lead to soil compaction. On the other hand, soil and water salinity causes reduction in the plant yield in addition to adverse effects on plants tolerance to the various stresses. The aim of this study was to investigate the interaction between soil compaction and salinity on the macronutrients uptake and wheat yield as well as its agronomic traits. The pot experiment was carried out on the loamy soil in a completely randomized block design with three replications. The treatments consisted of two salinity types (saline, EC = 6 dS/m and non-saline soil) and five levels of compaction; control, 5%, 10%, 15% and 20%. The results showed that soil compaction had significant effect on the amount of N, P and K in wheat grain, so that the uptake of N, P and K by grain has been decreased by increasing the compaction level of soil. Soil salinity had significant effect on N, P and K content in grain that the content of N, P and K has been diminished in the saline treatments compared to non-saline treatments. Results on the agronomic traits and yield of wheat also revealed that soil compaction and salinity had significant effect (p < 0.01) on straw weight, number of ears, number of grain, and thousand grain weight which caused reduction in these parameters. The interaction between compaction and salinity had only significant correlation (p < 0.01) with thousand grain weight leading to the decrement of thousand grain weight with increasing compaction levels, particularly in the saline treatment.